2006
DOI: 10.1158/0008-5472.can-06-1969
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Modulates the Glycogen Synthase Kinase-3β/β-Catenin Signaling Pathway and Attenuates Mammary Tumorigenesis of MDA-MB-231 Cells in Nude Mice

Abstract: Adiponectin is an adipokine that has pleiotropic beneficial roles in systemic insulin resistance and inflammation. Several recent clinical studies suggest that low serum levels of adiponectin are associated with increased risks of breast cancer. Here, we investigated the direct effects of adiponectin on breast cancer development in vitro and in vivo. Our results showed that adiponectin significantly attenuated the proliferations of two typical human breast cancer cells, MDA-MB-231 and T47D, in a cell type-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
217
5
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(238 citation statements)
references
References 52 publications
12
217
5
4
Order By: Relevance
“…This was suggested by the increase in cleaved caspase-8 and cleaved PARP in these cells. Other reports have found that apoptosis is involved in growth inhibition by Acrp30 by the use of TUNEL or annexin V assays (Kang et al, 2005;Dieudonne et al, 2006;Wang et al, 2006). We have extended those earlier observations by identifying increased cleavage of caspase-8 and PARP following treatment with Acrp30.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This was suggested by the increase in cleaved caspase-8 and cleaved PARP in these cells. Other reports have found that apoptosis is involved in growth inhibition by Acrp30 by the use of TUNEL or annexin V assays (Kang et al, 2005;Dieudonne et al, 2006;Wang et al, 2006). We have extended those earlier observations by identifying increased cleavage of caspase-8 and PARP following treatment with Acrp30.…”
Section: Discussionsupporting
confidence: 75%
“…Very little work has been done in this area with only one previous mention that gAcrp30 did not affect MDA-MB-231 cells growth but the data were not shown (Wang et al, 2006). In our hands the addition of gAcrp30 to MDA-MB-231 cells resulted in fewer cells after 48 hours but the reduction was not statistically significant.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In vitro studies have demonstrated that adiponectin induced apoptosis and inhibited migration and invasion of breast cancer cells (152,153). Furthermore, adiponectin suppressed the growth of the cancer in experimental breast cancer xenografts (146). Both AdipoR1 and AdipoR2 were detected in breast cancer tissue (154)(155)(156) and in breast cancer cell lines (157).…”
Section: Adiponectin and The Adiponectin Receptorsmentioning
confidence: 96%
“…Several studies have shown the negative effect of adiponectin on the proliferation of several cancer cell lines (144,146). Epidemiological studies, using serum adiponectin level as a measure of tissue exposure, suggested that adiponectin was a protective factor against breast cancer (147)(148)(149)(150)(151).…”
Section: Adiponectin and The Adiponectin Receptorsmentioning
confidence: 99%